Simple and usable : web, mobile, and interaction design - Colborne, Giles ([San Francisco, California] : New Riders, 2018)
"In a chaotic world, we all crave simplicity. We don't want to waste time re-configuring our smart phones, fumbling over digital printers, or plodding through online forms while deadlines bear down on us. We want technology that works. ... Simplicity is a discipline that can be learned. You'll learn how to strip away complexity by organizing, removing, hiding, and displacing. And you'll discover how to create focused, elegant user experiences that people will love"--adapted from back cover
Why are we here? -- Setting a vision -- Strategies for simplicity -- Remove -- Organize -- Hide -- Displace -- Before we go
Includes bibliographical references and index
Keywords: User interfaces (Computer systems) -- Design; User interfaces (Computer systems); Human-computer interaction